Physical activity in infancy and early childhood: a narrative review of interventions for prevention of obesity and associated health outcomes - Eichner-Seitz, Natalie; Pate, Russell R.; Paul, Ian M. (Frontiers in Endocrinology, 2023)
In the context of the childhood obesity epidemic, this narrative review aims to explore opportunities to promote physical activity (PA) between birth and age 5 years as well as the health outcomes associated with PA in early childhood. Although early childhood is an ideal time to promote healthy habits, guidelines for PA have often ignored early childhood given the limited evidence for children <5 years old. Herein we discuss and highlight infant, toddler and preschool age interventions to promote PA and prevent obesity both in the short and long-term. We describe novel and modified interventions to promote improved early childhood health outcomes, encompassing cardiorespiratory, muscle, and bone strengthening components necessary for short-term motor development and long-term health. We call for new research aimed at developing and testing innovative early childhood interventions that may be performed in home or childcare settings, monitored by parents or caregivers.